Correlation Analysis of Spiritual Intelligence on Physics Learning Outcomes - Hellen lie Grace Ghautama; Nandang Budiman; Sardin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
One of the biggest challenges faced by students is the ability to understand the essence and purpose of the learning process, including in physics subjects. The purpose of this study is to determine the relationship between spiritual intelligence and physics learning outcomes. The research method is a causal-correlational quantitative method. The data collection technique uses a spiritual intelligence questionnaire (SISRI-24) and physics learning outcomes in the form of mid-semester exam results. The sampling technique used is saturated sampling, namely the entire 12th grade population which is used as a research sample of 140 people. The instrument validity test uses product moment correlation and instrument reliability uses Cronbach's alpha. Spearman test statistical data uses SPSS version 27. The research findings show a positive correlation between spiritual intelligence and physics learning outcomes (r = 0.359). Analysis of the four dimensions of spiritual intelligence reveals that spiritual awareness has the most significant contribution (r = 0.396), followed by Critical Existential Thinking (r = 0.366), discovery of personal meaning (r = 0.226), and the conscious development (r = 0.210).